Urban development and societies in transit. The City as a representation of a chronic crisis - Ojeda, Rafael (2017)
This paper studied, from a historical and urban perspective, the transformations occurred in the cities in the last fifty years, in which a continuing process of agglomeration and an emerging and contradicting trend towards urban and social disagglomeration began to affect urban complexes. During this process, suburbia are cannibalized by the constant growth of metropolis, which are then transformed into expansive, chaotic and overwhelmed megalopolis, from counteracting trends, if we evaluate the situation of the world’s central cities compared to the suburban cities.